REVIEW AND ANALYSIS THE INDICATORS OF GREEN CITY WITH NDVI (STUDY CASE SHEIKH TAPPEH NEIGHBORHOOD IN URMIA) - Basiri, Mostafa; Someh, Mina Farokhi; Ghaderi, Bahman; Azim, Ali Zeynali (European Scientific Journal, ESJ, 2014)
Increasing urbanization and rapid population expansion and its specific problems such as air and water pollution, environmental degradation, increase in mental illness, housing, infrastructure, education and transportation and other problems of urban society more than ever threatens this contrary which is against the principles of sustainable development and green city projects is one of the urban environment measures in this field that has achieved success in the world. The idea is that the city is a place that forms human opportunities and abilities and in addition each city has its own life, soul and even its own special character therefore each city most be recognized as a whole and form it as a place of residence. Specific problems of urbanization has faced urban management with challenges in the field of population density, housing shortages, environmental degradation, pollution and supplying infrastructure services and facilities, and issues of the Green City project is more involved which results less public participating in cities sustainable development. This study analyzes the characteristics of green city’s indexes in Sheikh Tappeh neighborhood in Urmia. This is a descriptive -analysis study and data collection was conducted by library documents and field survey. According to survey results Sheikh Tappeh neighborhood is far from favorable indicators of health status and standards of green city and city planning and public participation is required.